X-Blind Qibla Accuracy Test with Google Earth Standard - Zahara, Ayu Putri; Azhari, Susiknan (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2024)
The problem related to the direction of the qibla is becoming more and more inclusive in the current era, considering that the suitability of the direction of the qibla is one of the prerequisites that must be met so that prayer can be considered valid according to sharia. In this Modern Era, there are Qibla directional instruments, both manual and digital-based such as Google Earth and Qibla compasses. In addition, there is also another innovation tool, namely X-Blind Qibla based on a modified compass with the addition of a buzzer. The author tries to examine the accuracy of the X-Blind Qibla with the standardization used, namely the Google Earth calibrator, based on a sample of mosques that have two typologies, namely the mosque that is right to the Qibla and the mosque that leads to the West. The research methodology stated in studying this problem is a qualitative method or field research. Based on the results of the study, it was found that the X-Blind Qibla deviated with an average value in the range of 1° 16' from the measurement results through Google Earth. The factors that affect the deviation are due to the effect of a large magnetic field, so that it has an impact on the movement of the compass magnetic needle. The value of the deviation is still understandable, if the reference in facing the qibla is the state of Saudi Arabia. This means that this tool can be applied in the practice of worship individually, even though it has not yet reached a high level of accuracy.